Power Imbalance And Patriarchal Control In Alison Goodman'S Eon And Eona: A Feminist Reading - Kamaruzaman, Nor Farah Anis (2016)
This study comprises a feminist reading of Alison Goodman's Eon and its sequel Eona through a conceptual framework that consists of various feminist and psychological tools. The review of related literature reveals that the fantasy genre is largely neglected by scholars as the genre is deemed as trivial and insignificant, and most studies on the fantasy genre are more focused on classic fantasy literature. The literature review also reveals that studies in the fantasy genre mostly focus on young girls and women's representation that often mirrors gender stereotypes. This study aims to fill the lacuna caused by the neglect of studies on power imbalance and patriarchal control in the fantasy genre. Objectives of the study include revealing power imbalance between genders, exposing patriarchal control over women, and determining the strategies of resistance used by women in their struggle against power imbalance and patriarchal control in the selected texts. The findings reveal that there is an imbalance of power between genders, whereby men hold more important roles in society, cultural traditions benefit men more than women, and women are often unfairly and ill-treated. The findings also reveal that women are being oppressed and subjugated by patriarchy through the use of violence, power, social norms, cultural traditions, and law.